Wake turbulence separation for Keflavik International Airport : Re-categorisation Requirements (RECAT-EU) - Toma Emilov Tomov 1976- (2019)
Keflavík International Airport has in recent years experienced constrained runway capacity during peak hours because of increased and intensified aircraft traffic. Two of the major factors that affect airport capacity are: the separation requirements due to wake turbulence between aircraft in approach for landing and Arrival Runway Occupancy Time. The latter is independent of the Wake Turbulence Categorisation of the aircraft, but restricts the time interval between two consecutive landings and thus the separation between landing aircraft. Currently, the Arrival Runway Occupancy Time of the airfield is a limiting factor for throughput capacity. RECAT-EU is a newer and modified wake separation scheme developed by EUROCONTROL which for the most part decreases the separation requirements, leading to more landings and departures and increased throughput capacity. This thesis presents a statistical evaluation of the effects from adopting the RECAT-EU scheme for Keflavík Airport in view of increased capacity, and estimate of the runway capacity constraints. The analysis of the RECAT-EU requirements for the airport, shows that the re-categorisation will have no effect on the separation requirement for 83,5% of the aircraft pairs from the traffic mix during peak hours. On the other hand, the average landing time interval could be reduced by 43 second for 14,9% of the aircraft after re-categorisation. However, this reduction places the distribution of landing time intervals well within the distribution of Arrival Runway Occupancy Times for the airfield. This establishes the Arrival Runway Occupancy Time as the limiting factor for potential increase of throughput capacity under the RECAT-EU scheme. Keflavíkurflugvöllur hefur undanfarin ár upplifað þvingaða flugbrautargetu á hámarkstíma vegna aukinnar flugvélaferðar. Helstu tvö þættir sem hafa áhrif á flugvallargetu eru: aðskilnaðarkröfur vegna kviku í aðflugi og heimildartíma flugvélanna á brautinni eftir lendingu. Síðarnefndu er óháð flokkunarkerfið vegna kviku, en ...